2016
DOI: 10.2495/afm160091
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of multiphase flow models applied to virtual flow metering

Abstract: This paper presents a performance evaluation of multiphase flow models when using these models on Virtual Flow Meters (VFM). Recently, VFM simulators have been identified as a technology capable of provide metering backup, monitoring for abnormalities of physical multiphase flow meters and also for production well allocation. Nevertheless, there are just a few studies found in the literature analysing the accuracy of different VFM models applied to multiphase flow metering. In the oil and gas industry it is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Cost: Quite expensive in installation and maintenance due to the fact that it has moving parts (Falcone et al, 2001;Patel et al, 2014;Hasanvand and Berneti, 2015). Durability: MPFMs may degrade owing to sand erosion or blockage (Marshall and Thomas, 2015) and may lead to years of inaccurate flow rate measurement if unchecked (Mokhtari and Waltrich, 2016). They also fail to measure flow rates accurately at water cut range of 40-60% or above 90% (Meribout et al, 2010) Health & Safety: Some MPFMs have radioactive sources as detectors which may affect workers (Hasanvand and Berneti, 2015;Roberts and Allen, 1993) Virtual flow meters (VFM)…”
Section: Space Requirementsmentioning
confidence: 99%
“…Cost: Quite expensive in installation and maintenance due to the fact that it has moving parts (Falcone et al, 2001;Patel et al, 2014;Hasanvand and Berneti, 2015). Durability: MPFMs may degrade owing to sand erosion or blockage (Marshall and Thomas, 2015) and may lead to years of inaccurate flow rate measurement if unchecked (Mokhtari and Waltrich, 2016). They also fail to measure flow rates accurately at water cut range of 40-60% or above 90% (Meribout et al, 2010) Health & Safety: Some MPFMs have radioactive sources as detectors which may affect workers (Hasanvand and Berneti, 2015;Roberts and Allen, 1993) Virtual flow meters (VFM)…”
Section: Space Requirementsmentioning
confidence: 99%
“…Several different approaches can be used to measure the multiphase flow, including but not limited to, conventional dedicated hardware-based flow meters [ 7 , 10 , 14 , 15 , 43 ], virtual flow meters [ 17 , 18 , 39 , 42 , 45 , 46 , 47 ], and distributed sensor flow estimations [ 8 , 37 , 40 , 48 ]. This paper focuses on providing a comprehensive review of the last approach, using distributed sensors with physical flow modelling and machine learning algorithms for multiphase flow estimation.…”
Section: Multiphase Fluid Flowmentioning
confidence: 99%
“…VFMs combine pressure, temperature, and other process control data from an existing sensors with multiphase fluid models, in order to estimate the fluid flow rates. However, the VFMs require extensive parameter tuning and active sensor calibration [ 16 , 17 , 18 ]. Parameter tuning in VFMs becomes complicated due to the complexity and ever-changing variables in the downhole environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to saying well production, a lot of numerical models can characterize it, starting from the well testing to decline curve analysis (DCA). Mokhtari and Waltrich [9] used the multiphase flow models to evaluate the well performance in virtual flow meter simulators and concluded that virtual flow meter simulators can provide accurate predictions for multiphase flow metering, such as flow rates of oil, gas, and water. Wang et al [10] used a multiscale flow model to analyze the well production performance in shale gas reservoirs with fractal geometry and concluded that there are six regimes of flow characteristics of type curves and a small fracture conductivity and a large region conductivity can lead to a large pressure depletion.…”
Section: Introductionmentioning
confidence: 99%